THE IMPLEMENTATION OF BLENDED LEARNING ASSISTED WITH EDMODO SOCIAL MEDIA AND ITS EFFECT ON ACCOUNTING LEARNING OUTCOMES - Abidah Dwi Rahmi Satiti; Yenni Vera Fibriyanti (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
This study aims to examine the effect of Edmodo Social Media Assisted Blended Learning implementation on accounting learning outcomes. This type of research is quasi-experimental research with a nonequivalent pretest and posttest control-group design. The population in this study were students of the Accounting Study Program of the Islamic University of Lamongan, Semester IV, Academic Year. 2019/2020. The research sample was taken as many as 2 groups consisting of 51 students for the experimental group (class IV B) and 54 students for the control group (class IV C). The sampling technique was carried out using simple random sampling. The data were collected using the method of documentation, observation, interviews, and tests. The data were analyzed using the t-test at a significance level of 5%. The results showed that there was an effect of Edmodo Social Media Assisted Learning Blended Learning policy implementing on accounting learning outcomes. The results of students studying accounting using the Blended Learning assisted by Edmodo Social Media show better results compared to the learning outcomes of students learning with conventional learning.